Disease patterns and incidence of immune-mediated disease in insured Swedish Nova Scotia Duck Tolling Retrievers - Bremer, H. D. (Vet Rec, 2015)
In this study, morbidity in insured Nova Scotia Duck Tolling Retriever (NSDTR) dogs from Sweden was investigated and compared with all other breeds and other retriever breeds. In addition to describing common morbidities in NSDTRs, the hypotheses that NSDTRs are predisposed to lymphoma, immune-mediated rheumatic disease (IMRD) and steroid-responsive meningitis-arteritis (SRMA) were tested. Included in the study were 445,336 dogs; of which, 2890 were NSDTRs that had been covered by veterinary insurance from the Agria Insurance Company (Stockholm, Sweden) at some point during the years 1995–2006. Incidences of various health problems were calculated using the number of veterinary visits as the numerator and the exact time at risk as the denominator. Overall, morbidity was higher in NSDTRs compared with all other breeds, but similar compared with other retriever breeds. The most common causes of veterinary visits in NSDTRs were injuries, gastrointestinal disease and locomotor disorders, with NSDTRs at increased risk of these compared with all other breeds. The incidences for IMRD, SRMA and lymphoma were significantly higher in NSDTRs than in all other dog breeds and all other retriever breeds. The study describes morbidity in NSDTRs, and identifies several disorders to which the breed is predisposed.